Answer:
the answer is 71,209 visitor
Step-by-step explanation:
12,629 + 24,290 + 24,290 = 71,209
1) -3(5x+2y=-3)⇒ -15x-6y=9
⇒ -9x=27
2(3x+3y=9)⇒ 6x+6y=18
2) -9x/-9=27/-9 ⇒ x=-3
3) 3(-3)+3y=9⇒ -9+9+3y=9+9⇒ 3y/3=18/3⇒ y=6
Answer: (-3,6)
Reasoning:
Step 1) In order to eliminate, first I had to multiple the first equation by -3 and the second by 2 so that when combining the equations y would cancel each other out so that I could solve for x. <em>Note: There are many combinations as to how you could multiple the equations so that either the x or y would cancel out.
</em>
Step 2) Once y is eliminated, solve for x.
Step 3) Now plug x back into one of the original equations and solve for y. <em>Note: Plug x back into one of the original equations, not the equations that were changed by multiplication,</em>
Answer:
2.2+3(3.4)
=2.2+10.2
=12.4
Step-by-step explanation:
Answer:
x = 16
y = 16√3
Step-by-step explanation:
sin(30 degrees) = 1/2
x = 32/2 = 16
cos(30 degrees) = √3/2
y = 16√3
Answer:
a force is described by its strength and by the direction in which it acts. -The strength of a force is measured in the SI unit called the Newton (N).
Step-by-step explanation: